Melatonin Derivative-Conjugated Formulations of Pd(II) and Pt(II) Thiazoline Complexes on Mesoporous Silica to Enhance Cytotoxicity and Apoptosis against HeLa Cells - Samuel Estirado; Diana Díaz-García; Elena Fernández-Delgado; Emilio Viñuelas-Zahínos; Santiago Gómez-Ruiz; Sanjiv Prashar; Ana B. Rodríguez; Francisco Luna-Giles; José A. Pariente; Javier Espino (MDPI AG, 2024)
The search for alternatives to cisplatin has led to the development of new metal complexes where thiazoline derivatives based on platinum(II) and palladium(II) stand out. In this sense, the Pt(II) and Pd(II) complexes coordinated with the thiazoline derivative ligand 2-(3,4-dichlorophenyl)imino-N-(2-thiazolin-2-yl)thiazolidine (TdTn), with formula [PtCl2(TdTn)] and [PdCl2(TdTn)], have previously shown good results against several cancer lines; however, in this work, we have managed to improve their activity by supporting them on mesoporous silica nanoparticles (MSN). The incorporation of metal compounds with a melatonin derivative (5-methoxytryptamine, 5MT), which is a well-known antioxidant and apoptosis inducer in different types of cancer, has been able to increase the cytotoxic activity of both MSN-supported and isolated complexes with only a very low amount (0.35% w/w) of this antioxidant. The covalently functionalized systems that have been synthesized are able to increase selectivity as well as accumulation in HeLa cells. The final materials containing the metal complexes and 5MT (MSN-5MT-PtTdTn and MSN-5MT-PdTdTn) required up to nine times less metal to achieve the same cytotoxic activity than their corresponding non-formulated counterparts did, thus reducing the potential side effects caused by the use of the free metal complexes.